Ocular fundus pulsations within the posterior rat eye : chorioscleral motion and response to elevated intraocular pressure - Augustin, Marco (2018)
A multi-functional optical coherence tomography (OCT) approach is presented to determine ocular fundus pulsations as an axial displacement between the retina and the chorioscleral complex in the albino rat eye. By combining optical coherence elastography and OCT angiography (OCTA), we measure subtle deformations in the nanometer range within the eye and simultaneously map retinal and choroidal perfusion. The conventional OCT reflectivity contrast serves as a backbone to segment the retina and to define several slabs which are subsequently used for quantitative ocular pulsation measurements as well as for a qualitative exploration of the multi-functional OCT image data. The proposed concept is applied in healthy albino rats as well as in rats under acute elevation of the intraocular pressure (IOP). The evaluation of this experiment revealed an increased pulsatility and deformation between the retinal and chorioscleral complex while increasing the IOP level from 15 mmHg to 65 mmHg. At IOP levels exceeding 65 mmHg, the pulsatility decreased significantly and retinal as well as choroidal perfusion vanished in OCTA. Furthermore, the evaluation of the multi-parametric experiment revealed a spatial correlation between fundus pulsatility and choroidal blood flow. This indicates that the assessed pulsatility may be a valuable parameter describing the choroidal perfusion.